2021
DOI: 10.1002/aoc.6338
|View full text |Cite
|
Sign up to set email alerts
|

Mycosynthesis of silver nanoparticles using Aspergillus caespitosus: Characterization, antimicrobial activities, cytotoxicity, and their performance as an antimicrobial agent for textile materials

Abstract: Mycosynthesis of stable silver nanoparticles (AgNPs) using Aspergillus caespitosus exo‐ and endo‐filtrates were obtained. Both exo‐ and endo‐AgNPs showed an absorbance peak at 410 nm, spherical, hexagonal, and anisotropic crystalline nanoparticles with 22–57 nm in size. FTIR analysis of mycosynthesized AgNPs showed presence of amide and carbonyl functional groups, which depicts the presence of peptides that involved in the synthesis and stability of AgNPs. Nitrate reductase activity was found to be 0.71 and 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Previous studies reported the biosynthesis of AgNPs with the Aspergillus family, including A. terreus, A. fumigatus, A.oryzae, A.niger, A.flavus, A. clavatus, and A. conicus [29][30][31]. These fungal strains possess efficient mechanisms for secreting extracellular enzymes, which help in the synthesis process by reducing the enzymes extracellularly or intracellularly [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported the biosynthesis of AgNPs with the Aspergillus family, including A. terreus, A. fumigatus, A.oryzae, A.niger, A.flavus, A. clavatus, and A. conicus [29][30][31]. These fungal strains possess efficient mechanisms for secreting extracellular enzymes, which help in the synthesis process by reducing the enzymes extracellularly or intracellularly [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, higher concentrations of AgNPs and lower average AgNP sizes are linked to higher and lower maximum wavelength values, respectively [ 87 ]. El-Bendary et al [ 88 ] detected a peak in the AgNPs spectra at 410 nm, providing evidence that AgNPs were produced by Aspergillus caespitosus. Here, Hashem et al [ 42 ] produced AgNPs by B. thuringiensis MAE 6 and had an SPR absorption band at 420 nm.…”
Section: Discussionmentioning
confidence: 99%
“…New drugs to combat this problem are therefore in great demand, but as past experience indicates, the time for resistance to new drugs to develop is often short. Conventionally, antibacterial drugs have been developed on the basis of their ability to inhibit bacterial multiplication, and this remains at the core of most approaches to discover new antibacterial drugs 1–5 . Nanotechnology and antibacterial materials have promise for the development of novel therapeutic interventions and effective preventive strategies against infections 6,7 .…”
Section: Introductionmentioning
confidence: 99%